PENGARUH BIMBINGAN KARIR DI SEKOLAH DAN STATUS SOSIAL EKONOMI ORANG TUA PADA PILIHAN KARIR SISWA - Triastuti, Triastuti; Mudjijanti, Fransisca (Educatio Vitae, 2015)
Career choice is important and will be considered students when they grow up. At the time like that sometimes students still feel confused career what really correspond to the potential and the situation himself. Because in the world of work a person is working not merely for financial satisfaction but a job that really fit and match the potential of the person who holds the job, so that the match will actually work with all his heart. This study aims to analyze the influence of career guidance at school and socio-economic status of parents on student career choice. Population used for this study are students of SMAN 6 Madiun 2014/2015 school year as many as 218 students with a sample of 109 students. Sampling technique used by the author is the technique  of Cluster Sampling, sampling was conducted with a random sample. In this study the authors propose three hypotheses: (1) the first minor hypothesis which says : there is significant influence career guidance in schools on student career choice, (2) a second minor hypothesis which says: there is significant influence of socio-economic status of parents towards election student’s career, (3) major hypothesis reads: significant influence career guidance in schools and socio-economic status of parents of student career choice. Data were analyzed using multiple linier regression techniques. Model of the regression line equation Y = 65,703 + 0,185 + 0,089 a subsequent analysis result showed that : (1) career guidance in schools affect the career choice of students who proved t > t table (4,420 > 1,983), (2) socio-economic status of parents affects the career choice of students who proved t > t table (2,068 > 1,983), (3) career guidance at school and socio economic status of parents affects the career choice of students who proved F count > F table (13,339 >3,08). Based on these results can be summarized as follows: (1) the first minor hypothesis is accepted, (2) a second minor hypothesis is accepted, (3) major hypothesis is accepted.